PKM BAGI GURU MADRASAH ALIYAH MIFTAHUL HUDA JLEPER MIJEN DEMAK DALAM PEMBUATAN MEDIA PEMBELAJARAN INTERAKTIF MELALUI APLIKASI PREZI - Sony Junaedi; Muslimah; Marya Ulfa (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Current learning after the pandemic is more towards the Hybrid learning method where this method combines online learning with face-to-face learning. In this learning, interactive learning media is needed by teachers. Prezi application is a software for internet-based presentation (SaaS). In addition to presentations, it can also be used as a tool to explore and share ideas on a virtual canvas. It is superior because this program uses the en:Zooming User Interface (ZUI), which allows Prezi users to zoom in and out of presentation media. The partner problem is that teachers at Madrasah Aliyah Miftahul Huda Mijen Demak still need training and assistance in making interactive multimedia. Therefore, the community service team at the Faculty of Language and Culture, University of 17 Agustustus 1945 Semarang conducted intensive communication with the manager of the MA Madrasah Aliyah Miftahul Huda to find solutions to these problems. There are three methods applied in this service, namely Presentation, Demonstration, and Practice Method. Presentation method is applied in the introduction of the Prezi Application, its benefits, and its application in making interactive learning media, Demonstration Method regarding the operation or use of the application and Practical Method where teachers practice directly making interactive learning media according to their respective subjects. After this service, teachers can position and use learning media as a needed component of a learning process. Learning media has an important role in increasing the effectiveness and efficiency of learning. Teachers are always required to be able to develop and use learning tools available in schools in accordance with current developments.